Relationship between physical activity, disability, and physical fitness profile in sedentary Latina breast cancer survivors. - Ortiz, Alexis; Tirado, Maribel; Hughes, Daniel C; Gonzalez, Velda; Song, JaeJoon; Mama, Scherezade K; Basen-Engquist, Karen (Physiotherapy Theory & Practice, 2018)
Objective: To report baseline data from a physical activity (PA) intervention for Latina breast cancer survivors, and assess the relationship between PA, fitness, and disability. Methods: Eighty-nine Latina breast cancer survivors from San Juan, PR and Houston, TX (age: 55.4 ± 9.9 years; BMI: 29.87 ± 5.62 kg/m2; ≥ 3 months post-treatment) participated in this study. At baseline participants completed fitness testing (six-minute walk test [6MWT], 30-second sit-stand; grip strength, lower and upper extremity and low back strength, shoulder range of motion, balance testing), and assessment of physical activity (PA) and disability. PA was assessed using the International Physical Activity Questionnaire (IPAQ). A subsample (n = 27) received an accelerometer to compare objective versus self-reported PA. Results: Participants exhibited low PA (M = 76.5 MET·minutes/week; SD = 183.4), poor fitness (6MWT M = 436.4 meters, SD = 99.1; 30s sit-stand, M = 11.6 stands, SD = 3.1), and no detectable disability. In an adjusted model lower extremity fitness was associated with PA, with a one repetition increase in sit-to-stand associated with 49 additional minutes of self-reported PA plus walking per week. The correlation between IPAQ moderate-vigorous PA and accelerometer was 0.38 (p = 0.047). Conclusion: Latina breast cancer survivors have low physical activity and fitness levels that increase their risk of disability, cardiometabolic comorbidities, and potential cancer recurrence.